2010
DOI: 10.1037/a0019985
|View full text |Cite
|
Sign up to set email alerts
|

Get smarty pants: Cognitive ability, personality, and victimization.

Abstract: Drawing on the victim precipitation model, this study provides an empirical investigation of the relationship between cognitive ability and victimization at work. We propose that people high in cognitive ability are more prone to victimization. In this study, we also examine the direct and moderating effects of victims' personality traits, specifically the 2 interpersonally oriented personality dimensions of agency and communion. Results support the direct positive relationship of cognitive ability and victimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 136 publications
4
65
0
2
Order By: Relevance
“…Research demonstrates that people with high cognitive abilities can become targets of resentment and envy because they trigger upward social comparisons (Kim & Glomb, 2010). People often choose ''standard setters'' who have high abilities as targets of comparison (Feldman & Ruble, 1981;Festinger, 1954), which can make these individuals targets of hostility among employees struggling to affirm their self-evaluations (Kim & Glomb, 2010).…”
Section: Moderating Effects Of Socio-political Costsmentioning
confidence: 98%
See 1 more Smart Citation
“…Research demonstrates that people with high cognitive abilities can become targets of resentment and envy because they trigger upward social comparisons (Kim & Glomb, 2010). People often choose ''standard setters'' who have high abilities as targets of comparison (Feldman & Ruble, 1981;Festinger, 1954), which can make these individuals targets of hostility among employees struggling to affirm their self-evaluations (Kim & Glomb, 2010).…”
Section: Moderating Effects Of Socio-political Costsmentioning
confidence: 98%
“…Research demonstrates that people with high cognitive abilities can become targets of resentment and envy because they trigger upward social comparisons (Kim & Glomb, 2010). People often choose ''standard setters'' who have high abilities as targets of comparison (Feldman & Ruble, 1981;Festinger, 1954), which can make these individuals targets of hostility among employees struggling to affirm their self-evaluations (Kim & Glomb, 2010). And cognitively complex individuals, who tend to constantly question underlying assumptions, may often be dismissed as too argumentative (Gruenfeld, Martorana, & Fan, 2000;Thomas-Hunt & Gruenfeld, 1998) or even as antagonistic and narcissistic (Tetlock, Peterson, & Berry, 1993).…”
Section: Moderating Effects Of Socio-political Costsmentioning
confidence: 99%
“…In summary, VPT posits that certain individuals, and individual personality types, may be more prone than others to victimization and abuse at the hands of authorities or significant others (Bowling, Beehr, Bennett, & Watson, 2010), with research in both work (e.g., Kim & Glomb, 2010) and non-work (Olweus, 1978) settings consistently identifying two types of victims. First, submissive victims are those that invite mistreatment and victimization from others because they are seen as passive, non-aggressive and unwilling or unable to defend themselves (Henle & Gross, 2013).…”
Section: Authoritarian Submission and Abusive Supervisionmentioning
confidence: 99%
“…For example, Henle and Gross (2014), applying victim precipitation theory, found that employees lower in emotional stability or conscientiousness are more likely to report higher levels of supervisor abuse because they experience more negative emotions. In short, low conscientiousness and emotional instability are seen as provocative personality traits; traits that are more likely to cause tension and hostility in interpersonal relationships (e.g., Kim & Glomb, 2010). Employees who exhibit such traits, therefore, are said to attract victimization -such as abusive supervision -because of the frustration and hostility these traits instill in their supervisors (Henle & Gross, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ukoliko se ima u vidu stabilna veza etiketiranja sa školskim uspehom, kao i društveno vrednovanje školskog uspeha osvedočeno učešćem u međunarodnim programima testiranja učeničkih postignuća (Trends in International Mathematics and Science Study -TIMSS: McComas, 2014; Program for International Student Assessment -PISA: OECD, 2009), iznenađuje nezainteresovanost psihologa za jednu od najučestalijih školskih etiketa povezanih sa školskim uspehom -za etiketu štrebera. Iako je reč o stereotipu poznatog značenja i široko rasprostranjene upotrebe, čak i van školskog konteksta (Darnon, Dompnier, Delmas, Pulfrey, & Butera, 2009;Exline & Lobel, 1999;Kim & Glomb, 2010), tek pre nekoliko godina pojavile su se prve socijalnopsihološke studije koje se bave ispitivanjem sadržaja i efekata ovog stereotipa.…”
unclassified